If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7y = -17 Solving 2x + -7y = -17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. 2x + -7y + 7y = -17 + 7y Combine like terms: -7y + 7y = 0 2x + 0 = -17 + 7y 2x = -17 + 7y Divide each side by '2'. x = -8.5 + 3.5y Simplifying x = -8.5 + 3.5y
| x^3-3x^2+8=0 | | 4y=33-4y | | 15+-29=n | | 4x+9-7x=9 | | -5x-8y=17 | | 9x^2+30x+16=0 | | 3x=6x-6 | | 10x+20=3(3x+2) | | 9(5y-4)-12y= | | -9+2=5u | | 3z+10z-17z= | | -16x+-12=-8 | | 9(5y-4)12y= | | 6x+6-7x=35 | | 3x=2x-2 | | -20x=-320 | | 4x-7=2x+21 | | -7x+9=c+1 | | 2(n-4)=28 | | 3-2y=5y+1 | | 4x+3=6x+17 | | 2y-8=20y+10 | | 10x=90 | | 1+3(5x-7)= | | x*3=2*x-2 | | 2x+5=5x-20 | | 3x+3y=-3 | | 8(3x-3)=2(12x+8) | | 5x+14-6x=78 | | y-4x^2=36 | | 7+3c+3+2c^3+-14= | | x+224.5=361.2 |